2021
DOI: 10.14712/23361964.2021.3
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the distribution of orchids – a review with examples from the Czech Republic

Abstract: The natural environment has been significantly altered by human activity over the past few decades. There is evidence we are now experiencing the sixth mass extinction, as many species of plants and animals are declining in abundance. We focused on the Orchidaceae because this plant family has experienced one of the biggest reductions in distribution. We investigated patterns in species richness and distribution of orchids, the rate and causes of their decrease and extinction, and factors influencing their occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
1
5
0
Order By: Relevance
“…The results indicated that ecological preferences and niche breadth vary among species, which is consistent with Tsiftsis et al [51], possibly because orchid germination niches are complex [71]. A better understanding of how niche breadth is associated with environmental gradients is crucial to species conservation, especially when considering the distribution of orchids [72]. These results revealed the niche breadth and the amplitude of geographical distribution of different Brachypetalum orchid species, which would be beneficial to set conservation priorities for the Brachypetalum orchid species in southwest China.…”
Section: Conservation Of Brachypetalum Orchids In Southwest Chinasupporting
confidence: 83%
“…The results indicated that ecological preferences and niche breadth vary among species, which is consistent with Tsiftsis et al [51], possibly because orchid germination niches are complex [71]. A better understanding of how niche breadth is associated with environmental gradients is crucial to species conservation, especially when considering the distribution of orchids [72]. These results revealed the niche breadth and the amplitude of geographical distribution of different Brachypetalum orchid species, which would be beneficial to set conservation priorities for the Brachypetalum orchid species in southwest China.…”
Section: Conservation Of Brachypetalum Orchids In Southwest Chinasupporting
confidence: 83%
“…Therefore, conservation measures could include increasing the protection and effective management of existing wetland areas and/or restoring degraded marshland areas within the north of the country. The limitation for our model is the exclusion of variables related to habitat, which is commonly used in other modeling studies [82,83]. However, due to the wide temporal range of occurrence data used, some from the 1990s, and the rapidly changing landscape in Armenia due to economic crises, illegal logging and the rise of mining activities, the use of habitat variables could reduce the overall accuracy of predictions.…”
Section: Discussionmentioning
confidence: 99%
“…The flowering and survival of many European orchid species is closely related to the resource status of plants, which is, in turn, influenced by appropriate site management [ 8 ]. Moreover, these species are expected to be at a greater risk of extinction as they are dependent on interactions with mycorrhizal fungi and pollinators, which are also being affected by habitat loss and climate change [ 9 , 10 ]. Orchids are particularly sensitive to environmental changes and are often amongst the first plant species to disappear in response to anthropogenic disturbances, making orchids relevant bioindicators of the ecological quality of ecosystems [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%